Modeling Contaminant Transport of Nitrate in Soil Column - Ekeleme, Anthony Chibuzo; Ekwueme, Benjamin Nnamdi; Agunwamba, Jonah Chukwuemeka (Emerging Science Journal, 2021)
Soil forms solution when it is in contact with water or any liquid. This soil solution disperses into the ground in different parts, at different velocities. Hence, the chemical contents of the soil are leached gradually from soil with infiltrating water. Soil parameter characterizing this phenomenon is referred to as Solute dispersivity. The objective of this study is to model contaminant transport of nitrate in soil, calibrate and verify the model derived. Dispersion studies were performed in the laboratory using soil columns filled with silver nitrate (AgNO3) solution. Samples were collected from the column outlet at intervals of 5minutes and the dispersion coefficient calculated. The dispersion coefficient calculated was incorporated into existing Notordamojo’s model and solved. Results obtained from the research showed that the R2values ranging from 0.741 to 0.896 and 0.484 to 0.769 were obtained for the modified model and the existing Notordamojo’s model respectively. The model verified with the experimental data showed predicted transport was in close agreement with experimental values having coefficient of correlation (r) ranging from 0.86 to 0.98. The difference between the experimental and predicted results, when expressed as a percentage of the experimental value was less than 5%. The study has established that the modified model which accounted for variability in dispersion coefficient offered a better approach than the conventional one. Doi: 10.28991/esj-2021-01290 Full Text: PDF